Optimization of Tiered Nursing Competency Supervision in the Central Surgical Installation of the Hospital - Nini Suhani; Hanny Handiyani; Kuntarti Kuntarti; Amelia Asmara (Indonesian Journal of Global Health Research, 2026)
Supervision of nurse competency in the operating room is an important component in ensuring compliance with standard operating procedures and patient safety. However, in some hospitals, supervision is still not optimal, often unscheduled, using manual forms, and lacking proper documentation. This residency project aims to improve the effectiveness of tiered nurse competency supervision to enhance patient safety in the hospital's central surgical installation. This case study uses Kurt Lewin's planned change approach consisting of three stages unfreezing, moving, and refreezing combined with management functions: planning, organizing, staffing, actuating, and controlling. Data collection was conducted through interviews, observations, and questionnaires. Planned change began with problem identification, followed by Fishbone analysis to determine root causes. Several improvement strategies were developed, including forming a supervision team, creating a routine supervision schedule through Google Sheets, and developing five digital supervision instruments using Google Forms. A trial implementation was carried out. Data were analyzed using descriptive statistics to summarize respondent characteristics and key variables, while inferential analysis was used to examine variable relationships and support achievement of the research objectives. The implementation of digital-based tiered nurse competency supervision increased the effectiveness of supervision and supported more structured competency development. The formation of a supervision team, scheduled supervision activities, and digitized instruments improved supervision quality. Trial results indicated competent performance aligned with SOPs based on observation checklists. Digital supervision forms proved efficient and practical, facilitating implementation, simplifying documentation, and accelerating evaluation of supervision outcomes.